ANALISIS PERMINTAAN TELUR BERDASARKAN JENIS DAN STRATA PENDAPATAN DI KALIMANTAN SELATAN - Suslinawati Suslinawati; Masyhuri Masyhuri; Mas Soedjono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2001)
This research wanted to know the consumer behavior in demand of egg as source of animal protein in South Kalimantan. In particular, this research aimed to identify and to know the price elasticity, cross elasticity and income elasticity at low, middle and high income groups, which were divided into the rural and urban areas and also were divided into egg of layer,